2017
DOI: 10.1128/aac.01880-16
|View full text |Cite
|
Sign up to set email alerts
|

Protracted Regional Dissemination of GIM-1-Producing Serratia marcescens in Western Germany

Abstract: The metallo-beta-lactamase GIM-1 has been found in various bacterial host species nearly exclusively in western Germany. However, not much is known about the epidemiology of GIM-1-positive Serratia marcescens. Here we report on a surprisingly protracted regional dissemination. In-hospital transmission was investigated by using conventional epidemiological tools to identify spatiotemporal links. Strain typing was performed using pulsed-field gel electrophoresis (PFGE) and whole-genome sequencing (WGS). Bayesian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Analysis of the genetic context revealed that bla GIM−1 is part of class 1 integron ( 85 , 88 , 89 ). This gene was carried by different conjugative plasmids but not typeable by PBRT ( 88 , 90 ). Until now, only one variant, GIM-2, of this carbapenemase has been described in E. cloacae in Germany ( 93 ).…”
Section: Minor Class B Carbapenemasesmentioning
confidence: 99%
“…Analysis of the genetic context revealed that bla GIM−1 is part of class 1 integron ( 85 , 88 , 89 ). This gene was carried by different conjugative plasmids but not typeable by PBRT ( 88 , 90 ). Until now, only one variant, GIM-2, of this carbapenemase has been described in E. cloacae in Germany ( 93 ).…”
Section: Minor Class B Carbapenemasesmentioning
confidence: 99%
“…WGS has been used to study S. marcescens virulence after wound infections and infection of snake bites (22). As well, WGS has been used to study the national dissemination of drug resistance elements and plasmids in S. marcescens throughout Germany, although only a limited number of isolates were subjected to NGS (16). The authors of that study also demonstrated that S. marcescens genomes can be used to generate genomic catalogues of antibiotic resistance genes.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, setting up a robust epidemiological wgMLST typing scheme is essential for monitoring and interrupting outbreaks in neonatal intensive care units (NICUs) as well as other medical settings. In addition, S. marcescens is capable of efficiently acquiring multiple resistance determinants (that are unreliable epidemiological markers), which adds to its clinical relevance (14)(15)(16)(17)(18). We have developed a proprietary wgMLST toolbox for S. marcescens based on publicly available WGS data.…”
mentioning
confidence: 99%
“…Although it is not possible to determine the steps involved in the evolution and transfer of these rearrangements found in S. marcescens SCH909, it is likely that this strain may be a source for potential LGT to other species. Knowing the remarkable number of niches that S. marcescens can occupy (Iguchi et al 2014;Abreo and Altier 2019), it is feasible to speculate on its essential role as a species able to capture new antimicrobial resistance genes and/or plasmids from the environment that can potentially be selected in the clinic (Park et al 2009;Zou et al 2011;Vilacoba et al 2014;Wendel et al 2017;Iasakov et al 2019). Taking into account that R1215 was also isolated in S. marcescens, these examples support the idea that this species has a high genomic plasticity adapted to acquisition of novel genetic elements from different niches, including antimicrobial resistance determinants relevant for successful maintenance in nosocomial strains.…”
Section: Discussionmentioning
confidence: 99%